2016
DOI: 10.1080/00016489.2016.1219049
|View full text |Cite
|
Sign up to set email alerts
|

Extended high frequency audiometry can diagnose sub-clinic involvement in a seemingly normal hearing systemic lupus erythematosus population

Abstract: In total, 70% were diagnosed with sensorineural hearing loss with extended high-frequency audiometry, overcoming the results obtained with pure tone audiometry (30.9%). Statistically significant correlations were found within the patients regarding sensorineural hearing loss related with age, disease activity and cryoglobulinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…5 The most common otologic symptom found in clinical studies of patients with SLE is sensorineural hearing loss (SNHL), the reported prevalence of which ranges from 6% to 70%. [10][11][12][13][14][15][16] 13 in a series of 84 patients, described bilateral and slowly progressive hearing loss; the same author in a previous paper described patients with SLE who developed sudden unilateral SNHL. 19 45 2007 55.5% SNHL for all frequencies (14%); SNHL for 500, 1000, and 2000 Hz (57%); SNHL for 4000 and 8000 Hz (28%) Khalidi et al 9 1 2008 n/a Profound bilateral SNHL for 500, 1000, 2000, and 3000 Hz; female Maciaszczyk et al 10 35 2011 71.4% Progressive SNHL with 500-, 2000-, and 4000-Hz frequency preservation Abbasi et al 11 45 2013 26.7% SNHL (11.1%), otorrhea (8.9%), tinnitus (6.7%) Lin et al 2 7168 2013 n/a Higher incidence of SNHL in women aged 34 years.…”
Section: Clinical Findingsmentioning
confidence: 95%
See 1 more Smart Citation
“…5 The most common otologic symptom found in clinical studies of patients with SLE is sensorineural hearing loss (SNHL), the reported prevalence of which ranges from 6% to 70%. [10][11][12][13][14][15][16] 13 in a series of 84 patients, described bilateral and slowly progressive hearing loss; the same author in a previous paper described patients with SLE who developed sudden unilateral SNHL. 19 45 2007 55.5% SNHL for all frequencies (14%); SNHL for 500, 1000, and 2000 Hz (57%); SNHL for 4000 and 8000 Hz (28%) Khalidi et al 9 1 2008 n/a Profound bilateral SNHL for 500, 1000, 2000, and 3000 Hz; female Maciaszczyk et al 10 35 2011 71.4% Progressive SNHL with 500-, 2000-, and 4000-Hz frequency preservation Abbasi et al 11 45 2013 26.7% SNHL (11.1%), otorrhea (8.9%), tinnitus (6.7%) Lin et al 2 7168 2013 n/a Higher incidence of SNHL in women aged 34 years.…”
Section: Clinical Findingsmentioning
confidence: 95%
“…The most common otologic symptom found in clinical studies of patients with SLE is sensorineural hearing loss (SNHL), the reported prevalence of which ranges from 6% to 70%. 10 16 Table 2 summarizes the different subtypes of hearing loss found in patients with SLE in multiple studies performed from 1995 to 2013 ( Table 2 ). Various authors have reported different pathways of SNHL in patients affected by SLE: hearing loss may either be slowly progressive or acute.…”
Section: Audiovestibular Disorders In Patients With Slementioning
confidence: 99%
“…Screening by title and abstract excluded 573 articles. A full-text review of remaining studies further eliminated 18 articles, leaving a total of 17 articles 68,10,11,1728 for inclusion in the final analysis. A diagram outlining the summary of the search process is shown in Supplementary Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…Only studies that provided sufficient data on audiological outcomes of interest were included in the meta-analysis. Of the 17 studies, 14 studies 68,10,17,1921,2328 were used to analyze the risk of HL in patients with SLE, nine studies 6,8,11,17,19,22,24,27,28 were used to pool frequency-specific air- and bone-conduction PTT data, and two studies 8,24 were used to compare the serological and clinical profiles of patients with SLE with and without HL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation